Media Representation of the Justice System: A Critical Discourse Analysis of Political Talk Shows - Younis, Sanam; Jami, Humaira; Nosheen, Nida (Journal of Development and Social Sciences, 2024)
The objective of the study is to examine how media representation of Pakistan’s justice system in political talk shows potentially shapes audience perception of justice system, employing a Socio-cognitive approach to Critical Discourse Analysis. Five political talk shows were selected based on viewership, audience reach, and content diversity. The sample included six episodes from each political talk show (N= 30 episodes) broadcasted every alternate Monday for three months. Findings revealed that political talk shows consistently offered a negative frame to its audience to make sense of the justice system. Discursive strategies such as presupposition, tag question, polarization, and presupposition were used in discourses to implicitly affect the audience’s perception of the judiciary. Results revealed media confirmation bias and cognitive dissonance play a pivotal role in molding public trust and confidence in the justice system. Future studies should consider the receptive as well as production side to indicate the extent to which audiences mirror media portrayals.